HUBUNGAN KARAKTERISTIK PEKERJA DENGAN TEKANAN DARAH PEKERJA WANITA TERPAPAR BISING SHIFT PAGI DI BAGIAN WEAVING (TENUN) AGUNG SAPUTRA TEX PIYUNGAN BANTUL YOGYAKARTA - Muchsin, .; Haryono, .; Rosyidah, . (Universitas Ahmad Dahlan, 2010)
Background :Agung Saputra Tex constitute industrialist weaving. In Agung Saputra TexPiyungan Bantul, there are some dangerous environmental risks factors which potentially in theweaving. Workers who do their activities in area whoes high noise intensity will suffer bloodpressure decrese. This research aimed to know: (1) the correlations between old age with bloodpreassure; (2) the correlations between working time with blood pressure; and (3) thecorrelations between body mass index (BMI) with blood pressure.Method : This was an observational research using cross sectional design. The population ofthis research was the worker of the weaving department. The subject were 25 workers. Theanalysis of data used bivariate correlations with pearson method.Results : The correlations showed that : (1) there was a significant correlation between old agewith systole blood pressure (r: 0,580 with p: 0,002) and a significant correlation between old agewith diastole blood pressure (r: 0,516 with p: 0,008) in the weaving Agung Saputra TexPiyungan Bantul; (2) there was a very significant correlation between working time with systoleblood pressure (r: 0,850 with p: 0,000) and a very significant correlation between working timewith diastole blood pressure (r: 0,646 with p: 0,000) in the weaving Agung Saputra TexPiyungan bantul; and (3) there was an ad for significant correlation between BMI with systoleblood pressure (r: 0,474 with p: 0,017) and a significant correlation between BMI with diastoleblood pressure (r: 0,397 with p: 0,049) in the weaving Agung Saputra Tex Piyungan Bantul.Conclusion : old age, working time, and body mass index are have a significant correlation withblood pressure decrease at the workers than often hit of noise in their working environment.Keyword: old age, working time, body mass index, blood pressure, systole, dyastole.